How Far Have We Developed Antibody-Drug Conjugate for the Treatment of Cancer? - Yu Jun Lim; Pei Sze Clarissa Lau; Shi Xuan Low; Shong Li Ng; Min Yee Ong; Huey Ming Pang; Zheng Yang Lee; Hui Yin Yow; Sharina Binti Hamzah; Renukha Sellappans; Jhi Biau Foo (MDPI AG, 2023)
Cancer, also known as malignant tumour or neoplasm, is a leading cause of death worldwide. One distinct feature from normal cells is that cancerous cells often overexpress protein on the cell membrane-for instance, the overexpression of human epidermal growth factor receptor 2. The expression of a specific protein on the cancerous cell surface acts as a marker that differentiates the normal cell and facilitates the recognition of cancerous cells. An emerging anticancer treatment, Antibody-Drug Conjugates (ADCs), utilises this unique feature to kill cancerous cells. ADCs consist of an antibody linked with a cytotoxic payload, mainly targeting the antigen found on cancerous cells. This design can increase the specificity in delivering the cytotoxin to the drug target, thus increasing the drug efficacy and reducing the side effect of cancer treatment due to off-target toxicities. There are tremendous quantities of clinical trials conducted to evaluate the safety and effectiveness of this magic drug in treating different types of cancers. However, only 12 ADCs have been approved by the FDA until now. This review provides the principles of ADCs and highlights the ADCs that FDA has approved. In addition, some of the ADCs that undergo clinical trials are discussed in this review. The application of computational techniques in addressing ADCs' challenges and neoantigen-targeted cancer vaccines is also highlighted. Although ADCs have been seen as promising magic drugs in cancer treatment, the problems such as toxicity, the stability of the linker, the specificity of an antibody with antigen, and so on, remain a challenge in developing ADCs.